Development Path Planning of Sports and Wellness Town under the Background of Computer Virtual Reality Technology - Lichun Chen; Bingxu Lu (Advances in Multimedia)
In order to improve the planning effect of the development path of the sports and wellness town, this article combines computer virtual technology to analyze the development path planning of the sports and wellness town and conducts research on the effect of the development path planning of the sports and wellness town through simulation research. Moreover, in order to deal with unknown time-varying actuator faults and uncertain disturbances of the system, an improved cost function is constructed in this article, which guarantees the expected performance index of the original system. In addition, this article uses the single-network ADP algorithm to solve the event-triggered HJB equation and adopts a new weight update law. Finally, an event-triggered near-optimal controller is obtained when evaluating the network’s success in approximating the improved cost function. The simulation study shows that the development path planning method of sports and wellness town based on computer virtual reality technology proposed in this article has a good effect and can effectively promote the progress and development of sports and wellness town.